THE EFFECT OF SERVICE QUALITY ON LOYALTY THROUGH CONSUMER TRUST AND SATISFACTION IN CLASSIC INTERIOR CREATIVE BUSINESSES IN MAKASSAR CITY - Ghinayah, A. Tsamratul; Kurniawaty, Kurniawaty; Nurung, Jumiaty (Journal of Entrepreneur, Business and Management, 2025)
This study aims to analyze the influence of service quality on consumer loyalty through trust and satisfaction in Classic Interior's creative business in Makassar City. This study uses a quantitative approach with a survey method of 122 respondents who are consumers of Classic Interior. The data analysis technique used is path analysis to test the direct and indirect influences between variables. The results of the study show that service quality has a positive and significant effect on consumer trust and satisfaction. Consumer trust and satisfaction have also been shown to have a significant effect on consumer loyalty. In addition, service quality has an indirect influence on loyalty through trust and satisfaction, where consumer satisfaction is the most powerful mediator in the relationship. This research emphasizes the importance of service quality improvement strategies that focus on creating consumer trust and satisfaction as a foundation in building long-term customer loyalty.Keywords: Service quality, trust, satisfaction, consumer loyalty, Classic Interior.